2014
DOI: 10.1038/srep06603
|View full text |Cite
|
Sign up to set email alerts
|

Adiabatic Quantum Simulation of Quantum Chemistry

Abstract: We show how to apply the quantum adiabatic algorithm directly to the quantum computation of molecular properties. We describe a procedure to map electronic structure Hamiltonians to 2-body qubit Hamiltonians with a small set of physically realizable couplings. By combining the Bravyi-Kitaev construction to map fermions to qubits with perturbative gadgets to reduce the Hamiltonian to 2-body, we obtain precision requirements on the coupling strengths and a number of ancilla qubits that scale polynomially in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
170
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 175 publications
(173 citation statements)
references
References 105 publications
(170 reference statements)
1
170
0
Order By: Relevance
“…It is not known to show the same direct dependence on the overlap of the initial guess state as QPE, which may allow it to solve different problems than the quantum phase estimation or variational quantum eigensolver in practice. In [51], Babbush et al show how to scalably embed the eigenspectra of molecular Hamiltonians in a programmable physical system so that the adiabatic algorithm can be applied directly. In this scheme, the molecular Hamiltonian is first written in second quantization using fermionic operators.…”
Section: Adiabatic Computationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not known to show the same direct dependence on the overlap of the initial guess state as QPE, which may allow it to solve different problems than the quantum phase estimation or variational quantum eigensolver in practice. In [51], Babbush et al show how to scalably embed the eigenspectra of molecular Hamiltonians in a programmable physical system so that the adiabatic algorithm can be applied directly. In this scheme, the molecular Hamiltonian is first written in second quantization using fermionic operators.…”
Section: Adiabatic Computationmentioning
confidence: 99%
“…In [51], Babbush et al reduce the locality of interaction terms using perturbative gadgets from the "bit-flip" family, first introduced in [53] and later generalized by [54]. In the supplementary material presented in a later paper analyzing the scaling of gadget constructions [55], it is shown that for bit-flip gadgets, λ k+1 /∆ k = O ( ) and…”
Section: Estimates Of Spectral Gap Scalingmentioning
confidence: 99%
“…In fact, when implementing ASP directly, i.e. when transforming the Hamiltonian to contain at most 2-qubit interactions, the Bravyi-Kitaev approach is crucial for the efficiency of the algorithm [56].…”
Section: A Adiabatic State Preparationmentioning
confidence: 99%
“…It turns out that for the efficient direct implementation of the ASP algorithm, the Bravyi-Kitaev transformation, which balances locality of occupation and parity information [54], is essential. When finishing this paper, we have learned about the very recent paper [56], which in detail describes the efficient algorithm relying on the BravyiKitaev transformation. We will therefore not discuss why use of the Jordan-Wigner transformation is not efficient, but rather refer the reader to [56].…”
Section: Analysis When Using Two-body Qubit Hamiltoniansmentioning
confidence: 99%
See 1 more Smart Citation